Association between the big five personalities and academic performance among grade 12 students at international high school in Thailand - Korn Boonyapison; Gobhathai Sittironnarit; Pinyo Rattanaumpawan (Scientific Reports)
Abstract The well-known Big Five personalities represent five personality characteristics including conscientiousness, extraversion, agreeableness, neuroticism, and openness. Previous literature confirmed that academic performance is associated with conscientiousness personality but there were some uncertainties in other personalities across study populations. The questionnaire-based study was conducted among Grade-12 students at an international high school in Thailand. The data on the Big Five Inventory (BFI) personality assessment, and other baseline characteristics were collected via online or paper questionnaires. One-hundred and thirty-three respondents were female with a median GPA of 3.61. There were 102 respondents with a GPA ≥ 3.61 in the academic achievement (AA)-group and 101 respondents with a GPA < 3.61 in the academic non-achievement (AN)-group. The AA-group had a significantly higher score in the conscientiousness domain while the score in the other four domains was comparable between both groups. Multivariate analysis identified the Conscientiousness personality domain and the female gender as the positively associated factors for academic achievement. Furthermore, a higher BMI and having extensive physical activities were identified as the negatively associated factors for academic achievement. Our study confirmed the universal association between conscientiousness personality and academic achievement among international students in Thailand. The study results would be helpful for policymaker to improve the educational program.